Perception, motivation, satisfaction and revisit intention on Muay Thai event as a sport tourist attraction - Popa, Arporn (2015)
The purpose of this study was to investigate foreign and domestic tourists’ perception,experience, satisfaction, motives and revisit intentions on Muay Thai event in Thailand. This study used the Leiper theory and the Theory of Planned Behavior (TPB), to examine tourists’ satisfaction, sport event attributes and sport motivation.Data were collected from 417 subjects, comprising foreign (50.1%) and domestic (49.9%) tourists attending Muay Thai events at Sanam Muay Rajadamnern stadium and Sanam Muay Lumpini stadium in Thailand. Foreign tourists’ monthly income was higher than domestic tourists. Event information sources (Marker Element) in Thailand among foreign and domestic tourists showed that both foreign and domestic tourists received Muay Thai information at their home or office via using several types of information sources such as from word of mouth communication, electronic communication, and mass communication. The mean scores of Muay Thai attributes actually experienced by foreign tourists ranged from 2.77 (SD = 1.95) to 5.92 (SD = 1.22),while mean scores for Muay Thai attributes for domestic tourists ranged from 4.00 (SD = 1.98) to 5.79 (SD = 1.21).The mean scores of Muay Thai attributes for both tourists were similar with the mean scores of tourists’ Motives for Attending Muay Thai events in Thailand from 2.38 (SD = 1.86) to 6.16 (SD = 1.55)for foreign tourists and from 4.07 (SD = 2.08) to 5.81 (SD = 1.50)for domestic tourists. In addition, the finding also indicated that all attributes dimensions were significantly correlated with behavioral intention to attend the Muay Thai event for both foreign and domestic tourists. However, the relationship between the attributes of Muay Thai experienced by foreign tourists were not significantly correlated with their attitudes,subjective norms and perceived behavioral control towards the event, while for domestic tourists, Muay Thai attributes were significantly correlated with these variables. The finding of this study suggests the best predictor of behavioral intentions in attending future Muay Thai event for domestic tourists was satisfaction (R2 change = 0.502), while foreign tourists was subjective norm (R2 change = 0.251).